Understanding the Therapeutic Approaches for Neuroprotection - Payal, Nazrana; Sharma, Lalit; Sharma, Aditi; Hobanii, Yahya H.; Ahmed Hakami, Mashael; Ali, Nemat; Rashid, Summya; Sachdeva, Monika; Gulati, Monica; Yadav, Shivam; Chigurupati, Sridevi; Singh, Abhiav; et al. (Current Pharmaceutical Design, 2023)
The term
Keywords: drug targeting